PUBLIC TIKTOK RESPONSES TO THE #STOPDEFORESTASI CAMPAIGN: AN ANALYSIS OF COMMUNICATION STYLE - Sri Wahyu Andini; Nurhanifah Nurhanifah (Program Pascasarjana UIN Sumatera Utara, 2026)
This study examines public responses to the #StopDeforestasi campaign on TikTok, focusing on the dynamics of communication style and the meanings produced by audiences in digital space. Using a qualitative content analysis approach, the data were collected through observation of content and user interactions on the account @zona.hening. The findings show that the campaign was able to generate strong emotional resonance through persuasive visuals and narratives, thereby encouraging public engagement in the form of comments, likes, and shares. However, such engagement did not fully represent in-depth understanding, as most responses remained affective and symbolic in nature. On the other hand, reflective, critical, and mobilizing responses were also identified, indicating the potential for a shift from slacktivism toward more substantive ecological awareness. This study confirms that the effectiveness of digital campaigns lies not only in their level of visibility, but also in the quality of the discourse they generate, although challenges remain in fostering critical and sustainable environmental literacy.